Clinical trials design, conduct and analysis - Meinert, Curtis L.; Tonascia, Susan (New York ; Oxford : Oxford University Press, 1986)
This provides a good reference for many practitioners of clinical trials, covering the design, eexecution and reporting of multicentre and single centre crossed trials that have a clinical event as an endpoint.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Clinical trials